Musical training as a potential tool for improving speech perception in background noise - Yates, Kathryn (2016)
Understanding speech in background noise is a complex and challenging task that causes difficulty for many people, including young children and older adults. Musicians, on the other hand, appear to have an enhanced ability to perceive speech in noise. This has prompted suggestions that musical training could help people who struggle to communicate in complex auditory environments. The experiments presented in this thesis were designed to investigate if and how musical training could be used as an intervention for improving speech perception in noise.